Анализа / мислења: Предлог- закон за антидискриминација - Анализа (Ревија за социјална политика/Journal of Social Policy, 2009)
The Republic of Macedonia is located before the adoption of a law for the prevention and protection against discrimination. In order to inform the expert and the general public about the proposed legal framework in detail, in the section: Analysis, various numbers of opinions and opinions regarding the Draft-law on Protection against Discrimination are given for this issue by official government officials, so and representatives of civic associations in Macedonia.